The Attitude of The Tablighi Jamaat Toward Covid-19 Pandemic - Abrar Abrar (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2021)
Covid-19 pandemic, which struck the world globally and rapidly, has caused significant fatalities. The government has implemented strict health protocols to suppress the spread of coronavirus. The reckless attitude of Tablighi Jamaat to hold “ijtima” amidst the massive spread of the virus is considered as an anomaly in preventing the Covid-19 pandemic and contradicts with the Fatwa of MUI (Indonesian Ulama Council) No. 14 of 2020 regarding the Implementation of Worship during Covid-19 Condition. This paper aims to find out the attitude of Tablighi Jamaat toward pandemic from the perspective of ḍarūrah (Naẓariyyat al-Ḍarūrah) theory by Wahbah al-Zuḥaylī. The writer gives a critical note of the arguments expressed by the Tablighi Jamaat and trying to show a more enlightening reconstruction of the fiqh (Islamic law) paradigm. The results of the study show that Tablighi Jamaat is a religious group that does not care about Covid-19. This attitude was triggered by the assumption that the existence of coronavirus is still in doubt. The doubt generates the understanding of fiqh that has not considered the corona issues as the ‘udhr category, which allows rukhṣah and abort the original law (‘aẓīmah), either in mashaqqah or ḍarūrah. The article assumes that the religious group’s narration that ignored the Covid-19 gives its members the feeling of peace and comfort, but it is counter-productive with the attempt to prevent the spread of Covid-19. It is necessary to reconstruct the fiqh paradigm to bring together science and religion, which is marked by the application of religious reasoning and sciences at the same time.